PERBEDAAN FAKTOR STRES DAN FAKTOR MAKAN TERHADAP KEJADIAN HIPERTENSI PADA LANSIA - Fidrotin azizah, Fidrotin azizah; atik setiyawan w, atik setiyawan w; untung budi, untung budi (Asuhan Kesehatan : Jurnal Ilmiah Ilmu Kebidanan dan Keperawatan, 2013)
Most of the elderly in the Village Corner suffering from hypertension . Consumer society , most of them choose instant foods , but these foods contain substances that can trigger hypertension . Besides economic difficulties , can cause stress that triggers hypertension . The purpose of this study was to determine differences in stress factors and eating factors on the incidence of hypertensionin the elderly . The study design used is analytic , the type of comparative cross-sectional approach . Its population , hypertension in the elderly Whole Village Corner , as many as 63 people , samples of 54 respondents and sampling techniques of probability sampling with simple random sampling . Independent variables ( factors and stress eating ) , and hypertensive elderly dependent variable . Data collection by questionnaire and analyzed using Mann Whitney U test trials were presented with tables and diagrams . Obtained , 34 respondents ( 63 % ) with a very high stress experienced moderate hypertension , Significance value of 0.263 and 16 respondents ( 29 % ) by a factor of eating high fat and salt moderate hypertension , Significance value of 0.029 . There are differences in the factors of stress and eating factors on the incidence of hypertension in the elderly . Elderly should reduce foods high in fat and salt , such as instant food , fried foods, bowel , seafood ( fish, squid , shrimp , crab ) and preserved foods ( fish science , anchovies , sardines , and shrimp paste ) . Keywords : Elderly , Hypertension , Stress Factor and Factor Eating .